2004
DOI: 10.1177/009102600403300109
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Findings on the Impact of Affirmative Action on the Training and Development of Black Managers for Corporate Organizations in South Africa

Abstract: The implementation of affirmative action is an important consideration in organizational dynamics and a strategic priority in South Africa. Training and developing blacks to fill managerial positions is also fraught with the concern to avoid tokenism and is compounded by the shortage of skilled black managers. Some organizations have adopted a proactive stance to accelerate the advancement of blacks into supervisory and managerial roles. Companies listed on the Johannesburg Stock Exchange and elicited from a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Even though there is empirical evidence that most organizations do not support legislated affirmative action, the same study found that firms that developed a written black management development policy were significantly more committed to the development of black managers (Jinabhai, 2004).…”
Section: Implications For South African Businessesmentioning
confidence: 94%
See 1 more Smart Citation
“…Even though there is empirical evidence that most organizations do not support legislated affirmative action, the same study found that firms that developed a written black management development policy were significantly more committed to the development of black managers (Jinabhai, 2004).…”
Section: Implications For South African Businessesmentioning
confidence: 94%
“…Organizations such the Black Management Forum (BMF) have proposed goals and timetables with specific focus on recruitment and promotion (Horwitz, 1996). While the organizational transformation is slower than many desire, there is strong empirical evidence that SA firms recognize the importance of training and development of black managers and are committed to supporting the principles of affirmative action (Jinabhai, 2004).…”
Section: Implications Of Increased Managerial Diversitymentioning
confidence: 99%